Zuhud in Tasawuf as Ethical Bureaucracy to Create Non Corrupted Behavior in Indonesia - Ali Saban (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2020)
Indonesia is a country that is very large and spacious with a wide variety of cultures and customs vary. A variety of cultures and customs is proof that Indonesia is built with very high ethical values. Ethics is a reflection of the Indonesian hierarchy of dignity and it should be maintained as a nation's personal identity. Along with the times, ethics comes with a more varied formation. Ethics is also developed in the dynamics of bureaucracy in Indonesia. But, after Indonesia's independence, the more ethical decline, particularly in relation to bureaucracy. To help smooth and in order that the research is comprehensive, the authors used a qualitative research approach as a tool. In addition, in order to balance the research, the author pairs this approach with the type of hermeneutic method, a method that examines the text and studies the behavior of the object. As a result, corrupt behavior becoming into behavior they always do, service to the community to be not optimal, as well as their responsibilities as officers are very low. In this case, I found the application and implementation of the zuhud principles are important in everyday life and/or ethics of their bureaucracy. Zuhud consists of principles of simplicity, integrity, and a strong sense of responsibility when it is done with sincerity and in accordance with the guidance Sharai. However, before the zuhud implemented and applied in bureaucratic ethics and everyday life, first need to be instilled positive attitudes toward zuhud value ​​themselves. Zuhud did not mean anti-world an sich, but the zuhud is able to present a moderate stance between the importance of the world and the hereafter as well.